Research priorities for the conservation of chondrichthyans in Latin America. (May 2022) - Becerril-García, Edgar E.; Arauz, Randall; Arellano-Martínez, Marcial; Bonfil, Ramón; Ayala-Bocos, Arturo; Castillo-Géniz, José L.; Carrera-Fernández, Maribel; Charvet, Patricia; Chiaramonte, Gustavo; Cisneros-Montemayor, Andrés M.; Concha, Francisco; Espinoza, Mario; et al.
Abstract: Latin American countries have a high diversity of sharks, rays, and chimaeras, yet many species are at high risk of extinction due to numerous threats. The conservation of chondrichthyans is key to achieving healthy and productive aquatic ecosystems, and countries in Latin America are increasingly recognizing the need for aligning conservation strategies across jurisdictions with similar ecological and socioeconomic challenges. Reflecting on the current state of knowledge and providing consensus expert opinion on research priorities are critical steps to ensure sound management and conservation strategies for chondrichthyans. The present study is a multinational collaboration by leading researchers in Latin America to identify the top-ten research priorities for the conservation of chondrichthyans within this region. Our results were highlighted from a total of 20 broader relevant topics including taxonomy and biology, ecological function, climate change and other stressors, contribution to local economies, and international collaboration. This constitutes the first comprehensive academic perspective on research priorities for chondrichthyans in Latin America which considers the varied perceptions and perspectives related to the management of sharks, rays, and chimaeras across the region and beyond. The main conservation implications highlighted by our study relate to the urgent need to implement, evaluate and/or improve management regulations based on scientific evidence and interdisciplinary research, especially in areas with little progress on the subject and/or where species threatened by extinction are distributed. Graphical abstract: Unlabelled Image Highlights: Chondrichthyans conservation in Latin America requires regulations based on research under an interdisciplinary approach. We provide an academic perspective on chondrichthyan research top-ten priorities in the region. Obtaining evidence is urgently needed to develop, apply, and improve successful sustainable management. These priorities are related to previous and novel knowledge in taxonomy, biology, fisheries, and sociology. Conservation can be compromised by mitigable factors such as pollution and climate change.